ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFATAR DI BEI TAHUN 2011-2015 - Kholidah, Asna Nur; Gumanti, Tatang Ary; Mufidah, Ana (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: This reserach aims to analyze the ability of financial ratios in predicting financial distress. It was a quantitative research using logistic regression model to analyze the ability of current ratio, return on assets, total assets turn over, and debt to assets ratio in predicting companies financial distress. The population of this research were the basic industry and chemical companies listed in Indonesia Stock Exchange. 52 companies satisfy the criteria. Sample were divided into two groups, 19 potentially financial distress companies and 33 not potentially financial distress companies. Result indicates that current ratio, return on assets, and debt to assets ratio acted as predictor of financial distress, while total assets turn over could not predict financial distress. Current ratio and return on assets have negative significant impact on predicting financial distress. Debt to assets ratio have positive significant impact on predicting financial distress.Keywords: Financial distress, Financial ratios, Logistic regression, Net profit